A Review of Sharia Economic Law on Mini Gas Station Business Practices (Case Study: in Nae Village, Bima City) - Agus Setiawan; Muhammad Rasyad Al Fajar; Muhammad Zia Ulhaq (JURNAL ECONOMINA, 2026)
This research aims to analyze the business practices of retail fuel filling stations, commonly known as "Pom Mini," in Nae Village, Bima City, from the perspective of Sharia Economic Law. The emergence of Pom Mini serves as a solution to the community's limited access to official gas stations; however, its operations often reside in a legal and sharia-compliance gray area. This study employs a descriptive qualitative method with a field research approach. Data were collected through in-depth interviews, direct observation of dispenser machines, and documentation. The results indicate that Pom Mini business practices in Nae Village do not fully comply with muamalah principles. The primary findings reveal elements of gharar (uncertainty) resulting from inaccurate measurements of dispenser machines that lack periodic calibration. Furthermore, operational safety aspects fail to meet Maqashid Sharia standards concerning the protection of life (hifz al-nafs). Although the pricing is socially accepted under the principle of mutual consent (an-taradhin) and custom (al-’urf), a transformation through business legality and technical standardization is required to ensure blessings (barakah) and public benefit (maslahah).